The mechanism for protecting the rights of internally displaced persons in Ukraine - Stepanenko, Nataliia; Dobrova, Kristina; Степаненко, Наталія В'ячеславівна; Доброва, Крістіна Олександрівна (ТОВ "Наукова установа "Правові горизонти", 2026)
The article examines the mechanism for protecting the rights of internally displaced persons (hereinafter – IDPs) in Ukraine in the context of full-scale war and post-war transformations. The author emphasizes that, despite the existence of a legal framework, in particular the Law of Ukraine “On Ensuring the Rights and Freedoms of Internally Displaced Persons” adopted in 2014, the system of protection of IDP rights remains fragmented, inconsistent, and insufficiently effective. Based on the analysis of scholarly sources and regulatory legal acts, the main problems in the implementation of IDP rights are identified, including the absence of a comprehensive model of legal protection, difficulties in accessing housing, employment, social and educational services, as well as weak integration of displaced persons into host communities. Particular emphasis is placed on the inconsistency of the national protection system with European human rights standards and the lack of effective mechanisms for the implementation of international conventions. A comparative analysis of international experience (Kenya, Nigeria, Ethiopia) has shown that effective protection of IDP rights is possible only through the integration of legislative, institutional, and socio-economic measures, as confirmed by the practice of implementing the Kampala Convention and the case law of the European Court of Human Rights. The article substantiates the need to modernize Ukraine’s mechanism for protecting the rights of displaced persons by harmonizing national legislation with international norms, strengthening the institutional capacity of public authorities, expanding the role of local self-government, introducing comprehensive integration programs, and actively engaging civil society. The article also highlights the role of judicial practice and law enforcement in shaping real guarantees for the protection of IDP rights, in particular through the analysis of national court decisions and administrative procedures that directly affect displaced persons’ access to effective legal remedies. Particular attention is paid to the issue of access to legal aid for IDPs as a key element in ensuring the principle of equality and non-discrimination in the context of armed conflict. It is concluded that only an interdisciplinary approach combining legal, managerial, and social instruments can ensure real, rather than formal, protection of IDP rights in Ukraine.
Механізм захисту прав внутрішньо переміщених осіб в Україні
Keywords: internally displaced persons; human rights; legal protection; social integration; international standards; European experience